Moyamoya Disease Associated With Morning Glory Disc Anomaly and Other Ophthalmic Findings: A Mini-Review - Wang, Yue-ye; Zhou, Ke-yao; Ye, Yang; Song, Fan; Yu, Jin; Chen, Jin-cao; Yao, Ke (Frontiers in Neurology, 2020)
Moyamoya disease (MMD) is a chronic cerebrovascular disease that is frequently resulting in intracranial ischemia or hemorrhage. Its concurrence with varying ophthalmic findings is relatively rare yet may lead to irreversible blindness. We performed a search and review of the literature to characterize the relevance of MMD (excluding moyamoya syndrome) and ophthalmic findings. As a result, a total of 38 articles identified from PubMed and Web of Science were included in this mini-review. Patients with MMD sometimes present with decreased visual acuity or visual field defects before the onset of symptomatic cerebrovascular dysfunction. The most predominant ophthalmic condition in MMD patients is the morning glory disc anomaly. Deficiency during neuroectodermal genesis and subsequent mesodermal changes may be responsible for the association between these two diseases. Thus, it may be beneficial for patients with MGDA to receive cerebral vascular examinations as the precaution against life-threatening intracranial angiopathy. Other ophthalmic findings reported in cases of MMD include retinal vascular occlusion, optic disc pallor, cortical blindness, etc. For most of the patients with MMD, retinal examinations would be recommended to prevent potential loss of vision. It is essential for both neurologists and ophthalmologists to be aware of the correlation between cerebrovascular diseases such as MMD and ocular manifestations to achieve a comprehensive diagnosis.